The Structural-Chemical Performance of Aluminium and Chromium based UO2 Advanced Technology Fuels - Jiménez, Pedro Foresti (2025)
The want for carbon neutral sources and the pressure of historical nuclear accidents leads to a search for safer and more efficient nuclear fuels. Advanced Technology Fuels aim to achieve this with the use of doped UO2 to achieve higher fission gas retention and improved pellet-cladding interaction, however, the knowledge about their behaviour preand post-irradiation is still not fully understood, particularly in the case of Al-doping. Therefore, this Master Thesis is devoted to understanding the chemical, microstructural and mechanical properties of Cr-, Al/Cr- and Al-doped UO2 model materials to support their use as nuclear fuels but also provide potential insight into their behaviour as spent nuclear fuel materials. In this study, a synthesis method for these materials using coprecipitation and high temperature sintering with doping amounts of 500, 1000, 1500 and 2000 molar ppm allowing for their comparison is developed and their microstructural, mechanical and chemical properties are analysed. Cr-, Al/Cr- and Aldoped UO2 ceramics with the doping amounts from 0 to 2000 molar ppm were produced and all found to be single phase consistent with the UO2 Fm3m structure via powder xray diffraction measurements. Rietveld analysis was used to quantify the incorporation of dopant cations within the UO2 lattice matrix. The analysis unveiled lattice contraction consistent with the relative size of the dopant cations Cr3+ and Al3+ in which the incorporation is correlated to grain growth. To examine this improved grain growth, electron microscopy via scanning electron microscopy with backscattered electrons and electron backscatter diffraction measurements were performed. These results indicated variable grain growth that is dependent upon the position of the pellets and the dopant used. In particular, it was observed for 2000 ppm Al- and Al/Cr-doped UO2 a reduced grain size at the rim of the pellets. This reduced grain size at the rim is attributed to the higher volatility and lower solubility of Al2O3 compared to Cr2O3. The microhardness and fracture toughness of these materials were determined through Vicker’s indentation combined with image analysis of the indent and cracks. It was found that Al-doped materials exhibited consistent microhardness and relatively higher fracture toughness than Al/Cr doped materials. In contrast Cr-doped materials presented variable fracture toughness and microhardness due to the materials not being at complete dopant saturation, unlike the Al/Cr and Al. Consequently, the mechanical properties highlight the importance of considering solubility of dopants and their relative amounts for addition in determining mechanical properties. Overall, the thesis provides key novel insights into the preparation, chemical behaviour, microstructural performance and mechanical stability of Cr-, Al/Cr- and Al-doped UO2 model materials relevant to advanced next generation fresh and spent nuclear fuels.